Numerical estimation of inter line power flow controller based on injection model of synchronous voltage sources - Shahriari, Amidaddin; Mokhlis, Hazlie; Karimi, Mazaher; Bakar, Ab Halim Abu; Illias, Hazlee Azil; Kazeminejad, Mohammad; Palizban, Omid (Numeryczna estymacja mieogonekdzyliniowego regulatora przepływu mocy - modelowanie synchronicznych źródeł napieogonekcia, 2013)
This paper presents the estimation model of Inter-Line Power Flow Controller (IPFC) based on injection model of synchronization voltage source. The linear model of voltage source inverter is used to estimate steady-state operation of Inter-Line Power Flow Controller. The proposed model can keep the capability of IPFC with the acceptable accuracy. The active and reactive power flow at receiving end line could be controlled separately in this proposed model. Furthermore, the proposed model has these abilities to decrease the reactive power flow and control of the sending bus voltage at the same time. The validation of the proposed method is shown by using two machine systems to estimate suitable approximation of power flow at receiving end line.